Desain dan Karakterisasi Penggunaan Sensor Efek Hall UGN3503 untuk Mengukur Arus Listrik pada Kumparan - Johan Wahyudi, Gurum Ahmad Pauzi, Warsito (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2013)
Hall effect is a deflection of electricity phenomena (electrons) in the conductor plate because of the magnetic fields effect. UGN3503 is a sensor with Hall effect principle, In this study UGN3503 sensor used to measure the electric current in the coil Leybold P6271 with non destructive method. Microcontroller processing results is an electric current measured by system and displayed on a LCD 20x4 in Amperes. Research data were taken 40 times with variations of the electric current ranging from 1 Amperes to 4,9 Amperes. calculated based on these data the average error that occurred in the measurement gauge amounted to 1,44%. Keywords: Hall Effect, UGN3503, ATMega8535.